A Web-Based Decision Support System For Evaluating The Best Homestay Using The Simple Additive Weighting (SAW) Method - Rolando Rusdan Rivai Rolando; Medi Triawan; Lendy Rahmadi (International Journal of Health Engineering and Technology, 2026)
The rapid growth of the tourism sector in Pagar Alam City has increased the demand for quality accommodation, particularly homestays. As recorded by the Pagar Alam City Tourism Office, 132 homestays are currently in operation, offering tourists a wide range of alternatives with varying prices, facilities, locations, cleanliness, and service quality. However, the absence of an integrated evaluation system makes it difficult for tourists to objectively compare available options and select the most suitable homestay. This study aims to develop a web-based Decision Support System (DSS) for selecting the best homestay using the Simple Additive Weighting (SAW) method. The research employed the Waterfall software development model, consisting of requirements analysis, system design, implementation, testing, and system deployment. The study used 13 homestays that participated in the 2022 Best Homestay Assessment organized by the Pagar Alam City Tourism Office as the research sample, ensuring reliable assessment data and measurable quality indicators. Five evaluation criteria were applied, namely price, facilities, location, cleanliness, and service, each assigned a predetermined weight based on its level of importance. The SAW method was implemented to normalize criterion values, calculate preference scores, and rank homestay alternatives according to their overall performance. The developed system successfully generated objective and transparent recommendations for the best homestays through an accessible web-based platform. Functional testing confirmed that the system performed all required processes accurately, including data management, normalization, preference calculation, and ranking generation. The findings indicate that the proposed decision support system effectively supports tourists in making informed accommodation choices while assisting tourism stakeholders in conducting a more systematic, efficient, and objective homestay evaluation process in Pagar Alam City.